Advances of the small molecule drugs regulating fibroblast-like synovial proliferation for rheumatoid arthritis - Tong, Yitong; Li, Xinyu; Deng, Qichuan; Shi, Jianyou; Feng, Yibin; Bai, Lan (Frontiers in Pharmacology, 2023)
Rheumatoid arthritis (RA) is a type of chronic autoimmune and inflammatory disease. In the pathological process of RA, the alteration of Fibroblast-like synovial (FLS) and its related factors is the main influence in the clinic and fundamental research. In RA, FLS exhibits a uniquely aggressive phenotype, leading to synovial hyperplasia, destruction of cartilage and bone, and a pro-inflammatory environment in synovial tissue for perpetuation and progression. Evidently, it's a highly promising way to target the pathological function of FLS for new anti-RA drugs. Based on this, we summed up the pathological mechanism of RA-FLS, and reviewed the recent progress of small molecule drugs, including the synthetic small molecule compounds and natural products targeting RA-FLS. In the end, there were some views for further action. Compared with MAPK and NF-κB signaling pathways, JAK/STAT signaling pathway have great potential for research as targets. A small number of synthetic small molecule compounds have entered the clinic to treat RA and were often used in combination with other drugs. Meanwhile, most natural products are currently in the experimental stage, not the clinical trial stage, such as Triptolide, etc. There was an urgent need to unremittingly develop new agents for RA.